Thermosensitivity profile of malignant glioma U87-MG cells and human endothelial cells following γ-Fe2O3 NPs internalization and magnetic field application. Issue 19 (5th February 2016) - Hanini, A.; Lartigue, L.; Gavard, J.; Schmitt, A.; Kacem, K.; Wilhelm, C.; Gazeau, F.; Chau, F.; Ammar, S.
Abstract : In this study the thermosensitivity of malignant glioblastoma cells (U87-MG), incubated with superparamagnetic 10 nm sized polyol-made γ-Fe2 O3 particles and exposed to an alternating magnetic field (700 kHz, 23.10 kA m −1 ) for 1 hour, is evidenced. Abstract : In this study we evaluate the thermosensitivity of healthy endothelial cells (HUVEC) and malignant glioblastoma (U87-MG) to magnetic hyperthermia (ac-magnetic field of 700 kHz, 23.10 kA m −1 ) for 1 hour with and without the presence of superparamagnetic 10 nm sized polyol-made γ-Fe2 O3 nanoparticles (NPs). Interestingly, despite their reduced size, NPs exhibit high magnetization, close to that of the bulk material, in relation to their high crystalline quality. In practice, they ensured an efficient heating capacity, leading to about 20% and more than 50% cell death of HUVEC and U87-MG lines, respectively, when hyperthermia assays were achieved in the presence of these NPs. Magnetophoresis and X-ray fluorescence spectrometry measurements evidenced a more important internalization of NPs in U87-MG than in HUVECs. Surprisingly both cell lines reached the same maximal temperature, namely 42 °C, after hyperthermia treatment suggesting a higher thermosensitivity of the former compared to the latter, establishing the fact that polyol-made γ-Fe2 O3 NP assisted hyperthermia is a harmful agent to glioma treatment.